Pendeteksi Volume Air pada Galon Berbasis Internet of Things dengan Menggunakan Arduino dan Android - Denny Kuriando; Agustinus Noertjahyana; Resmana Lim (Jurnal Infra, 2017)
Internet of things has a concept that aims to expand the benefits connected in a continuous internet connection on an ongoing basis. The method used by Internet of Things is automatic control without distance. Implementation currently gallon control of water is still done by looking at the state of gallons and then gallons turn when the water in the gallon is already empty. With the internet of things can be implemented a water volume detector that can monitor the state of the gallon from a distance through a smartphone. To make the manufacture of water volume detection required tools such as water flow sensors, microcontroller or other tools that are then connected to the internet. For interaction relationship of water flow sensor, microcontroller, or other tool of help through internet used Android application. This Android application is used to facilitate users to access the internet anywhere. This Android application is made by using Android studio and microcontroller made with Arduino programming using C language. Microcontroller used is WeMos D1 R2 which has been contained ESP8266 in it.The result of this water volume detection development is the microcontroller can transmit sensor data to the Ubidots server so that the application can retrieve sensor data on the Ubidots server. Users can view the gallon state in real time and are also given a notification when the gallon water volume is below alert level. Users can also view reports of gallons per month.